Virgin crossing borders : feminist resistance and solidarity in translation - Ergun, Emek (Professor) (Transformations (University of Illinois (System). Press), 2023)
"The Turkish-language release of Hanne Blank's Virgin: The Untouched History is a politically engaged translation aimed at disrupting Turkey's heteropatriarchal virginity codes. In Virgin Crossing Borders, Emek Ergun maps how she crafted her rendering of the text and draws on her experience and the book's impact to investigate the interventionist power of feminist translation. Ergun's comparative framework reveals translation's potential to facilitate cross-border flows of feminist theories, empower feminist interventions, connect feminist activists across differences and divides, and forge transnational feminist solidarities. As she considers hopeful and woeful pictures of border crossings, Ergun invites readers to revise their views of translation's role in transnational feminism and examine their own potential as ethically and politically responsible agents willing to search for new meanings. Sophisticated and compelling, Virgin Crossing Borders reveals translation's vital role in exchanges of feminist theories, stories, and knowledge"--